Sex differences in behavioral responses during a conditioned flight paradigm - Borkar, Chandrashekhar D.; Dorofeikova, Mariia; Le, Quan-Son Eric; Vutukuri, Rithvik; Vo, Catherine; Hereford, Daniel; Resendez, Alexis; Basavanhalli, Samhita; Sifnugel, Natalia; Fadok, Jonathan P. (Behavioural brain research, 2020)
•Male and female mice do not differ in conditioned flight behavior.•Female mice exhibit more freezing behavior.•Rearing, self-grooming, and tail rattling behavior changes across days.•Male mice exhibit more rearing and grooming behavior.•Female mice exhibit more tail rattling behavior. Females exhibit greater susceptibility to trauma- and stress-related disorders compared to males; therefore, it is imperative to study sex differences in the mode and magnitude of defensive responses in the face of threat. To test for sex differences in defensive behavior, we used a modified Pavlovian fear conditioning paradigm that elicits clear transitions between freezing and flight behaviors within individual subjects. Female mice subjected to this paradigm exhibited more freezing behavior compared to males, especially during the intertrial interval period. Female mice also exhibited more freezing in response to conditioned auditory stimuli in the last block of extinction training. Furthermore, there were sex differences in the expression of other adaptive behaviors during fear conditioning. Assaying rearing, grooming, and tail rattling behaviors during the conditioned flight paradigm yielded measurable differences across sessions and between males and females. Overall, these results provide insight into sex-dependent alterations in mouse behavior induced by fear conditioning.